Live worksheets matematika: dalam perspektif siswa menurut model motivasi ARCS - Nissa, Ita Chairun; Febrilia, Baiq Rika Ayu; Astutik, Fitri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research is a survey that aims to categorize students’ responses to Live Worksheets as interactive math worksheets. Subjects are 11th grade high school students who have attended math class in Google Classroom. They have studied a math topic with the help of interactive worksheets linked from Live Worksheets to Google Classroom. At the end of the topic, students were asked to fill out a questionnaire about how well the interactive math worksheets in Live Worksheets maintained or improved their learning. Responses were measured on five Likert scales and categorized into four elements of the ARCS model of motivation: Attention, Relevance, Confidence, and Satisfaction. The four elements are further divided into their constituent components. Data analysis shows that the four elements are in the ’good’ criteria with their components being in the ’good enough’ to ’very good’ criteria. The results of this study then become a reference for the mathematics teacher at the school to revise the design of interactive worksheets that can really help students understand mathematics, especially during distance learning that relies on technology.